Ana and her web?: an investigation into Internet use in adults with an eating disorder - Harrison Yuill, Faye (2013)
The aim of the study was to explore the use of the internet in adults with an eating disorder. Previous evidence has suggested that people with an eating disorder are likely to access websites that are associated with their eating disorder (Wilson, Peebles, Hardy & Litt, 2006). The researcher hypothesised that the scores on measures of stage of change, self-efficacy for recovery, eating disorder symptoms, and perceived social support would be different depending upon the type of website accessed. A cross-sectional survey was administered online.